Doing well & doing good the challenge to the Christian capitalist - Neuhaus, Richard John 1936-2009 (Doubleday, 1992)
For too long, Neuhaus argues, Christianity has had nothing to say to Wall Street or to Main Street. Drawing on the writings of Pope John Paul II, Neuhaus has written a spirituality of economic enterprise meant for the businessman and the intellectual alike.
Keywords: Katholische Kirche; Catholic Church -- Doctrines; Catholic Church. -- Pope (1978-2005 : John Paul II). -- Centesimus annus; Kapitalismus; Religion; Wirtschaft; Capitalism -- Religious aspects -- Catholic Church; Christian sociology -- Catholic Church; Church and social problems -- Catholic Church; Economics -- Religious aspects -- Catholic Church; Liberty -- Religious aspects -- Catholic Church; Social ethics; Christentum